Protective effects of honeybee products against COVID-19: a review. Issue 1 (October 2021) - Ciric, J; Djordjevic, V; Baltic, T; Brankovic Lazic, I; Petronijevic, R; Spiric, D; Trbovic, D
Abstract: According to the World Health Organization, coronavirus disease (COVID-19-global pandemic) is defined as highly contagious viral infection that causes severe acute respiratory syndrome-coronavirus-2 (SARS-CoV2). This disease is very rapidly transmitted among humans. To date, 30 May 2021, at least 170, 689, 920 confirmed cases of COVID-19 have been reported while global deaths reached 3, 550, 093 (https://www.worldometers.info/coronavirus/ ). In Serbia (to date 30 May 2021) at least 712, 046 confirmed cases of COVID-19 have been reported, while deaths reached 6, 844 and recovered 694, 492. Also, Serbia is at the top of the list of country vaccination rates against COVID-19. New concerns regarding vaccine safety and efficacy are coming with the mutated strains of SARS-CoV-2 virus. Natural products of known antiviral activity can be used for various therapeutic purposes. Honey, propolis, pollen, bee bread, bee venom and royal jelly might potentiate the immune system of patients and reduce their susceptibility to COVID-19 infection.